A new species of African legless skink, genus Acontias Cuvier, 1816 “1817” (Squamata: Scincidae) from Serra da Neve inselberg, south-western Angola - Marques, Mariana P.; Parrinha, Diogo; Tiutenko, Arthur; Lopes-Lima, Manuel; Bauer, Aaron M.; Ceríaco, Luis M.P. (African Journal of Herpetology, 2023)
During a recent survey of the Serra da Neve inselberg in south-western Angola, a population of legless skinks of the genus Acontias was found. Only three species of this genus have been recorded for the country so far–A. occidentalis, A. kgalagadi and A. jappi. Using an integrative approach and combining molecular and morphological data we found that the Serra da Neve population represents a new species, closely related to species such as A. percivali and some members of the A. occidentalis species complex. In this paper, we describe this population as a new species, Acontias mukwandosp. nov. and provide brief comments on its conservation and biogeography.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Acontinae; endemism; speciation; systematics; taxonomy